2017
DOI: 10.1001/jamapsychiatry.2017.0659
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Medication Use for Attention-Deficit/Hyperactivity Disorder and Risk of Motor Vehicle Crashes

Abstract: IMPORTANCEMotor vehicle crashes (MVCs) are a major public health problem. Research has demonstrated that individuals with attention-deficit/hyperactivity disorder (ADHD) are more likely to experience MVCs, but the effect of ADHD medication treatment on the risk of MVCs remains unclear.OBJECTIVE To explore associations between ADHD medication use and risk of MVCs in a large cohort of patients with ADHD. DESIGN, SETTING, AND PARTICIPANTS For this study, a US national cohort of patients with ADHD (n = 2 319 450) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
98
2
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 128 publications
(103 citation statements)
references
References 30 publications
1
98
2
2
Order By: Relevance
“…It has been shown that stimulant medication reduces health risk behavior, such as alcohol and drug abuse and vehicle accidents among patients with ADHD. Similarly, medical treatment of ADHD among patients with type 1 diabetes might result in better metabolic control.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that stimulant medication reduces health risk behavior, such as alcohol and drug abuse and vehicle accidents among patients with ADHD. Similarly, medical treatment of ADHD among patients with type 1 diabetes might result in better metabolic control.…”
Section: Discussionmentioning
confidence: 99%
“…We concluded that the diabetes care should target the specific needs of these patients in order to ensure their quality of life and metabolic control and thus prevent long-term complications 30. It has been shown that stimulant medication reduces health risk behavior, such as alcohol and drug abuse31 and vehicle accidents32…”
mentioning
confidence: 99%
“…Pharmacotherapy has been shown to improve executive function, reduce risk-seeking behavior, and decrease rates of criminality in individuals with ADHD. 53,54,[57][58][59] ADHD treatment has also been shown to decrease trauma rates with dramatic reduction in motor vehicle trauma, 42,60 and it can decrease the risk of substance use-related disorders. 59,61 A 2012 meta-analysis of long-term outcomes of ADHD treatment found 50% to 100% improvement in driving, obesity, self-esteem, social functioning, academics, drug use/addiction, antisocial behaviors, and use of services for treated vs untreated patients.…”
Section: Treatment Reduces the Risk Of Morbidity And Mortality And Inmentioning
confidence: 99%
“…Adolescents may not adhere to or may discontinue their medication 110,142 even though it helps prevent risky behaviors and increases academic performance. 60,139,143,144 In adolescence, we may also begin to see patients diverting (swapping with or selling to peers) or misusing their short-acting stimulants. Engaging the adolescent patient and parents in shared decision making about ADHD treatment and monitoring for signs of diversion and misuse can help improve medication adherence and enhance outcomes.…”
Section: Adolescentsmentioning
confidence: 99%
“…2 Treatment of adult ADHD improves functioning 3,4 and quality of life 5 and reduces the risk of adverse outcomes such as accidents 6 and problems related to substance abuse. 7 Women on treatment for ADHD may therefore wish to continue their medications during pregnancy in order to continue to experience the benefits of treatment.…”
mentioning
confidence: 99%